How Do Filamentous Pathogens Deliver Effector Proteins into Plant Cells? - Petre, Benjamin (Public Library of Science, 2014)
Fungal and oomycete plant parasites are among the most devastating pathogens of food crops. These microbes secrete effector proteins inside plant cells to manipulate host processes and facilitate colonization. How these effectors reach the host cytoplasm remains an unclear and debated area of plant research. In this article, we examine recent conflicting findings that have generated discussion in the field. We also highlight promising approaches based on studies of both parasite and host during infection. Ultimately, this knowledge may inform future broad spectrum strategies for protecting crops from such pathogens.